Radial rotation of cell-pair under beam mode coupling effect of microcavity cascaded single fiber optical tweezers - Ji Zhaoqi; Jiang Chunlei; Chen Peng; Yao Linzhi; Zhang Minghui; Shi Qizan; Zhao Cun; Wang Xiufang; Sun Yu; Dong Taiji (Nanophotonics)
This article presents a control method for radial cell-pair rotations using a single-fiber manipulation technique that combines microcavity cascade optical tweezers with optical fiber mode coupling technology. It explores the mechanisms of cell manipulation under the influence of mode coupling and capillary fluid forces. By controlling the angle of fiber twisting and utilizing the birefringence effect along with the principle of beam mode coupling, it is possible to achieve precise and regular variations in the energy of the LP21 mode beam spot, thereby altering the magnitude and direction of the forces acting on the cell-pair, which induces a tendency for rotational motion. The microcavity cascade optical tweezers provide a small capillary fluid force and serve to isolate the cell-pair from the external environment, allowing it to respond to changes in beam spot energy within a stable microcavity space, thus enabling controllable rotations in both direction and angle. The combination of microcavity cascade optical tweezers with beam mode coupling technology achieves, for the first time, radial cell-pair rotations driven by a single fiber, which holds significant implications for the study of polarized cell migration as well as the investigation of tissue fluidity and connectivity dynamics in cancer prediction.